Bullying and negative appearance feedback among adolescents: Is it objective or misperceived weight that matters?. (28th December 2017) - Lee, Kirsty; Dale, Jeremy; Guy, Alexa; Wolke, Dieter
ABSTRACT: This study investigated (1) whether involvement in bullying as a bully, victim or bully‐victim was associated with objectively measured overweight or underweight, or whether it was related to weight misperception (i.e., inaccurate perceptions), and (2) whether appearance‐specific feedback mediated the relationship between bullying and weight misperception. In Stage 1, 2782 adolescents aged 11–16 years from British secondary schools were screened for peer bullying and victimisation. In Stage 2, 411 adolescents with weight and height data (objective n  = 319, self‐report n  = 92) also self‐reported on their weight perception and appearance‐specific feedback. Neither bullying nor victimisation were related to objective underweight or overweight. Victims were at increased odds of overweight misperception, while bully‐victims were at increased odds of underweight misperception. Additionally, there was an indirect effect of appearance feedback on overweight misperception in bully‐victims. Both victims and bully‐victims are at increased risk of weight misperception, posing further detrimental effects to their health and wellbeing. Highlights: Objective weight status was not associated with being a victim, bully‐victim, or bully. Misperceived weight status was associated with being a victim and bully‐victim. Negative appearance feedback was associated with overweight perception in bully‐victims. Bullies tended to accurately perceive their weight.